2018
DOI: 10.3122/jabfm.2018.05.180041
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Electronic Health Record (EHR) Tool for Integrated Behavioral Health in Primary Care

Abstract: Background: Integrating behavioral health into primary care can improve care quality; however, most electronic health records are not designed to meet the needs of integrated teams. We worked with practices and behavioral health (BH) clinicians to design a suite of electronic health record tools to address these needs (“BH e-Suite”). The purpose of this article is to examine whether implementation of the BH e-Suite changes process of care, intermediate clinical outcomes, and patient experiences, and whether it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 27 publications
2
44
0
Order By: Relevance
“…The access to accurate and complete clinical information is the main component of effective decision making 69. This is facilitated by decision-support EHR tools - BPAs - and designed for behavioral health integration with the needs of health care institutions and the benefits of improving the patient experiences,36 for instance, alcohol use 30. The system can be used to update the current condition of a patient as input to obtain a corresponding recommendation for medical tests, possible diseases, and treatment plans 69.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The access to accurate and complete clinical information is the main component of effective decision making 69. This is facilitated by decision-support EHR tools - BPAs - and designed for behavioral health integration with the needs of health care institutions and the benefits of improving the patient experiences,36 for instance, alcohol use 30. The system can be used to update the current condition of a patient as input to obtain a corresponding recommendation for medical tests, possible diseases, and treatment plans 69.…”
Section: Discussionmentioning
confidence: 99%
“…The EHR application improves the process,36 trustworthiness, safety, and efficiency of patient care delivery 29. Hence, implementing standardized policies, processes, and procedures for an appropriate health care data management system that advances the quality of health services and efficiency,34,37 avoids non-value adding activities,34 and ensures major quality and safety improvement 16,17,23,34.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study suggested that 3 prominent barriers to the adoption of mental health care EHRs should be considered: complex privacy-related laws and regulations, inadequate financial incentives, and assistance for psychiatric providers [2]. Another study suggested that EHRs designed for mental health care must satisfy the needs of clinicians for the successful uptake of necessary information and improvement in patient experience to disseminate them efficiently [13]. Although a number of studies have evaluated the effectiveness of EHRs, there have been few studies on barriers and facilitators to the adoption of mental health care EHRs from the perspective of mental health clinicians, nurses, pharmacists, and administrative professionals in mental hospitals.…”
Section: Previous Studiesmentioning
confidence: 99%
“…The TRIAD method led to the development of the BH e-Suite, which was found to be acceptable and easy to use by BHCs in subsequent pilot testing, and improved care delivery. 21 This tool was subsequently adopted by OCHIN Epic for release to OCHIN’s 640 CHCs, suggesting that the TRIAD method is promising as a research and development approach.…”
Section: Discussionmentioning
confidence: 99%